The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1515/amcs-2017-0021
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the GPC Control Quality Using Non–Gaussian Statistical Measures

Abstract: This paper presents an alternative approach to the task of control performance assessment. Various statistical measures based on Gaussian and non-Gaussian distribution functions are evaluated. The analysis starts with the review of control error histograms followed by their statistical analysis using probability distribution functions. Simulation results obtained for a control system with the generalized predictive controller algorithm are considered. The proposed approach using Cauchy and Lévy α-stable distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 34 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…Above hypotheses confirm earlier observations done for other type of industrial control 5 and simulation analysis performed for the GPC predictive control. 24 Automated and autonomous evaluation of indexes without reflection about loop environment may be misleading. Visual inspection of data, like trends, histograms, correlations and X-Y relations, is strongly recommended.…”
Section: Conclusion and Open Issuesmentioning
confidence: 99%
“…Above hypotheses confirm earlier observations done for other type of industrial control 5 and simulation analysis performed for the GPC predictive control. 24 Automated and autonomous evaluation of indexes without reflection about loop environment may be misleading. Visual inspection of data, like trends, histograms, correlations and X-Y relations, is strongly recommended.…”
Section: Conclusion and Open Issuesmentioning
confidence: 99%
“…Non-Gaussian statistical [157] and fractal [158] methodologies have been investigated for the GPC predictive control algorithm. Linear [159] and nonlinear [160] DMC predictive control have been assessed using integral, statistical, information, and fractal measures.…”
Section: Data-driven Approachesmentioning
confidence: 99%
“…Used variables may exhibit fat tails, asymmetric properties or varying broadness. The aspects of fat tails [6] and broadness (described by the variance or scaling) [7] have been already addressed in previous research. Observed non-symmetric properties of control variables are relatively frequent, especially in non-linear cases.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that even simple linear MPC configuration requires alternative CPA approach, such as fractal [48] or non-Gaussian [6]. Nonlinear industrial control generates even more serious challenges for reliable MPC monitoring.…”
Section: Introductionmentioning
confidence: 99%